The Influence of Service Quality and Facilities with Pertamina Gas Station Consumer Satisfaction 21,385.08. Manna City, South Bengkulu Regency - Pegi Ade Putra; Siti Hanilah; Eska Prima Monique Damarsiwi (Penerbit Jurnal Indonesia, 2022)
This revolution era of oil fuel ( BBM) represent requirement of whole world society. Oil fuel not again bizzare goods because without existence of oil fuel hence entire/all activity and production will be burdened by for example motor and car can be run with existence of oil. Target [done/conducted] by this research is to know influence of[is quality of facility and service to satisfaction of consumer exist in SPBU 21.385.08 Town Paradise fruit Sub-Province of Bengkulu south. In this research of used sampel counted 120 people by using method of purvosive sampling with the meaning taken at random which is coincidence come to SPBU buy oil fuel. Result of got research by using meotde analyse doubled linear regression [is] the quality of facility and service have an effect on signifikan to satisfaction of consumer that is both variable of x its value of him 0,000. Base decision making if variable of signifikansi less than 0,005 hence expressed to have an effect on Value of VIF and of Tolerance both [of] variable of[is quality of facility and service both of the same value of VIF below/under 10 and tolerance above 1,0. Inferential that quality of is same facility and service - is same do not have symptom of multikolonearitas. From result of enumeration by using SPSS can know by coefficient value of determinasi of R is 0,843 so that R square equal to 0,711. Matter this means that Variable value of X have an effect on to variable ( Y) equal to 71,1 % while the rest 28,9 % influenced by other variable which do not check in this research